(untitled) (Research, Society and Development, 2020)
Through a bibliographic review in order to verify what companies are doing to minimize social impacts in the 4th industrial revolution, also known as Revolution 4.0, it can be seen that: It is assumed that, in the coming years, new technologies will affect workers, and that this workforce prefers robots rather than being replaced by people they consider a threat and not that robots can be a threat to the economic future. Some efforts are being made to assist the worker to reenter the labor market, such as: preparing employment laws and policies and promoting human resources, including in the faculties creativity and convergence (China), Germany to meet the changes including new manufacturing and technology concepts and improving problem solving, creativity and innovation skills, applying factory learning concepts to dominate complex situations and unconventional schools, however those who are dismissed will be alienated, and will have great challenge for their replacement in the market and may take a long time to reinsert them.